Pengaruh profesionalitas guru dalam minat litrerasi baca siswa di era gen alpha - Munawir Munawir; Anisah Dwi Rakhman; Hafsho Wahyuningrum (Universitas Sebelas Maret, 2025)
Teachers are an influence in the success of students in reading skills. The influence of teacher professionalism in students' reading literacy interest. Teachers adjust the character of students in the alpha gen era with the methods to be taught. Teachers encourage students' enthusiasm in increasing students' interest in reading literacy. The purpose of this research is to explain the influence of teacher professionalism in students' reading literacy interest in the alpha gene era with its various characteristics. The strategies that teachers do in order to increase student enthusiasm in reading literacy interest. The method used in data collection is literature and document review. The instruments used are literature documents in the form of journals, articles and books. Based on the results of the study, it shows that the characteristics of gen alpha vary, teachers must be able to adjust by using strategies that attract students' attention to improve reading literacy skills.